The Rights of Leave of Absence of Civil Servants - Adil Bucaktepe (Jurnal Cita Hukum, 2024)
Civil officials have several rights conferred by the Constitution as well as by laws and regulations to facilitate the successful execution of their responsibilities. These rights encompass the entitlement to the appointment, provision of service and security, retirement, resignation, the ability to initiate a complaint or legal action, the formation of a trade union, collective bargaining, leave from employment, special considerations in prosecution and trial, protection against accusations and defamation, as well as the right to remuneration and travel expenses. This paper will succinctly examine the overarching rights of federal servants and will thoroughly analyze the "right to leave." Article 50 of the Constitution of the Republic of Turkey ensures employees' entitlement to a day off, while statutory regulations govern paid weekly and annual leave as well as official holidays. Furthermore, Article 23 of the Government Servants Law No. 657 mandates that government servants are entitled to leave under conditions and durations prescribed by law, enabling them to take leave for rest or other purposes. Within this framework, the legislation governs five types of leave: yearly leave, special leave, sick leave, compassionate leave, and unpaid leave. This study employs a qualitative methodology encompassing two primary approaches: a literature review and a legal analysis. The literature review is conducted by examining several academic sources, books, and journals pertinent to the rights of civil servants, particularly the right to quit. This analysis examines the evolution of leave-related rules and regulations across various international contexts and their implementation in Turkey. The legal framework is employed to examine the statutes and regulations pertaining to the rights of government servants in Turkey, encompassing Article 50 of the Constitution and Law No. 657. This article assesses the alignment between legal theory and practice on the right to leave. The study's findings indicate that, despite the legal promise of leave for federal personnel, its execution frequently encounters challenges, particularly concerning the duration and requisite administrative conditions. This paper presents an extensive analysis of government servants' leave rights in Turkey and proposes enhancements for the execution of this right to promote equity and well-being among civil servants.